Molecular survey on tick-borne pathogens and Leishmania infantum in red foxes (Vulpes vulpes) from southern Italy - Sgroi, Giovanni; Iatta, Roberta; Veneziano, Vincenzo; Bezerra-Santos, Marcos Antonio; Lesiczka, Paulina; Hrazdilová, Kristýna; Annoscia, Giada; D'Alessio, Nicola; Golovchenko, Maryna; Rudenko, Natalie; Modrý, David; Otranto, Domenico (Ticks and tick-borne diseases, 2021)
Red foxes (Vulpes vulpes) have been recognised to harbour and transmit a wide range of tick-borne pathogens (TBPs) including those of zoonotic concern. To investigate the prevalence and the distribution of TBPs and of Leishmania infantum in foxes (n = 244), spleen samples were collected within the frame of a multi-regional wildlife health surveillance program in Italy. A combined PCR/sequencing approach was performed for the detection of Anaplasma spp., Babesia spp., Borrelia spp., Ehrlichia spp., Hepatozoon spp. and L. infantum DNA. Overall, 146 foxes (59.8 %, 95 % CI: 53.6-65.8) tested positive for at least one pathogen with Hepatozoon canis being the most prevalent (i.e., n = 124; 50.8 %, 95 % CI: 44.6-57.0), followed by Babesia vulpes (n = 20; 8.2 %, 95 % CI: 5.4-12.3), different spirochete species from Borrelia burgdorferi sensu lato complex (n = 9; 3.7 %, 95 % CI: 1.9-6.9), Ehrlichia canis and L. infantum (n = 7; 2.9 % each, 95 % CI: 1.4-5.8), Anaplasma platys (n = 4; 1.6 %, 95 % CI: 0.6-4.1), Anaplasma phagocytophilum ecotype I and Candidatus Neoehrlichia sp. (n = 3; 1.2 % each, 95 % CI: 0.4-3.5). All samples scored negative for Babesia canis and Borrelia miyamotoi. This study revealed the presence of spirochetes from B. burgdorferi s.l. complex, Ca. Neoehrlichia sp., A. platys and A. phagocytophilum ecotype I in red fox population from Italy, underling the necessity to monitoring these carnivores, mainly because they live in contact with dogs and humans. Data on the tick fauna circulating on wildlife species will complement information herein obtained, instrumentally to establish preventive strategies for minimizing the risk of infection for animals and humans.
Keywords: Animals; Female; Prevalence; Tick-Borne Diseases; leishmanióza viscerální; Leishmania infantum; Leishmaniasis, Visceral; ženské pohlaví; DNA bakterií; DNA, Bacterial; Italy; Itálie; lišky; nemoci přenášené klíšťaty; prevalence; DNA, Protozoan; Male; Foxes; protozoální DNA; zvířata; mužské pohlaví